2015
DOI: 10.1007/s00267-015-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

European Tamaricaceae in Bioengineering on Dry Soils

Abstract: International audienceWe tested the bioengineering capabilities and resistance to drought of cuttings of two typical riparian species of Mediterranean and Alpine streams scarcely used in soil bioengineering: Myricaria germanica (L.) Desv. and Tamarix gallica L. We conducted two experiments, one ex situ and one in situ, with different drought treatments on cuttings of these two species in comparison with Salix purpurea L., a willow very commonly used in bioengineering. The biological traits considered were resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
4
1
2
Order By: Relevance
“…Bioengineering techniques take advantage of the natural properties of plants to stabilise the bank with the combined effects of roots and canopy cover [Gyssels et al, 2005]. These actually very old techniques [Evette et al, 2009;Anstead et al, 2012] present many advantages: they are low-cost treatment [Watson et al, 1997], they have a small carbon footprint compared to riprap [Von Der Thannen et al, 2017], they support biodiversity and ecological functions in the riparian aquatic and terrestrial habitats created [Anstead and Boar, 2010;Cavaillé et al, 2013;Evette et al, 2013;Cavaillé et al, 2018], they can increase the resilience of riverbanks against the effects of climate change [Anstead et al, 2012;Lavaine et al, 2015], and overall, they can resist very aggressive flow conditions: for instance, fascines were observed to resist shear stress up to 250 N/m² [Lachat, 1994;Gerstgraser, 2000]. These qualities make them an ideal candidate for the restoration of low-cost rivers in remote areas [Tamrakar, 2010;Dhital et al, 2013;Tamrakar et al, 2014;Dhital and Tang, 2015] or in highly urbanized areas where green solutions are welcome [Ng et al, 2011;Zhang and Chan, 2012;Zhu and Zhang, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Bioengineering techniques take advantage of the natural properties of plants to stabilise the bank with the combined effects of roots and canopy cover [Gyssels et al, 2005]. These actually very old techniques [Evette et al, 2009;Anstead et al, 2012] present many advantages: they are low-cost treatment [Watson et al, 1997], they have a small carbon footprint compared to riprap [Von Der Thannen et al, 2017], they support biodiversity and ecological functions in the riparian aquatic and terrestrial habitats created [Anstead and Boar, 2010;Cavaillé et al, 2013;Evette et al, 2013;Cavaillé et al, 2018], they can increase the resilience of riverbanks against the effects of climate change [Anstead et al, 2012;Lavaine et al, 2015], and overall, they can resist very aggressive flow conditions: for instance, fascines were observed to resist shear stress up to 250 N/m² [Lachat, 1994;Gerstgraser, 2000]. These qualities make them an ideal candidate for the restoration of low-cost rivers in remote areas [Tamrakar, 2010;Dhital et al, 2013;Tamrakar et al, 2014;Dhital and Tang, 2015] or in highly urbanized areas where green solutions are welcome [Ng et al, 2011;Zhang and Chan, 2012;Zhu and Zhang, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Bioengineering of soils utilizes certain features of flora components and incorporates particular features of structures with flora [4]. The resultant systems and elements have potential advantages and disadvantages, which have to be considered before choosing them for application.…”
Section: Introductionmentioning
confidence: 99%
“…Soil bioengineering seeks to mimic the natural functioning of riparian vegetation, i.e. strengthening riverbanks through the use of the soil fixation properties of roots and protecting the soil via a carpet effect as well as by slowing down water flow (Li & Eddleman, 2002;Lavaine et al, 2015). Recently, several studies have demonstrated the effectiveness of soil bioengineering structures in resisting shear stress (e.g.…”
Section: Introductionmentioning
confidence: 99%